Apoptosis in cancer: from pathogenesis to discovery of advanced selective Bcl-2 family inhibitors - Samaa Abbas; Nermin S. Abdou; Deena S. Lasheen; Dalal A. Abou El Ella (Ain Shams University, 2019)
Cancer is a genetic disease characterized by two features: unregulated cell growth and tissue invasion (metastasis). It can be viewed as the result of a succession of genetic changes during which a normal cell is transformed into a malignant one. Evasion of cell death, apoptosis, is one of the essential changes in a cell that cause this malignant transformation. Hence, reduced apoptosis or its resistance plays a vital role in carcinogenesis. The Bcl-2 family of proteins regulates the mitochondrial apoptotic pathway. Disease states arise upon deregulation of the Bcl-2 family of proteins, where cell death is either promoted or evaded; one of the most common tactic cancer cells utilize to promote survival is anti-apoptotic protein overexpression. Specifically, Bcl-2 overexpression has been shown to be a major chemoresistance factor in a number of human cancers, and for this reason, Bcl-2 targeting is a pharmacologic priority in the quest to reactivate cell death for therapeutic benefit in cancer.